Top Management Team Diversity and Company Performance: The moderating effect of Organization Life Cycle - Velinov, Emil; Malý, Milan (Journal of Eastern European and Central Asian Research (JEECAR), 2016)
The research paper examines the moderating impact of Organizational Life Cycle on the relationship between Top Management Team Diversity and Company Performance. The study first elaborates and establishes the theoretical link between organization lifecycle and composition of management elites. Second, a quantitative empirical study is conducted to test the OLC stages moderating impact on the upper echelons diversity and firm performance of the top companies in the Czech Republic. A detailed procedure is developed to accurately classify organizations at different lifecycle stages, drawing extensively on existing literature and scales. Paper findings state that more mature the company becomes, more diversified the senior management is regardless the firm performance. Also, the industry dynamism impact has its own role in the relationship between the organization life cycle and senior management diversity which is expressed by the paper findings as well.